Why Apply a Hierarchical Predictive Processing Framework to Music Perception and Performance? - Michael, John; Wolf, Thomas (Empirical Musicology Review, 2015)
In this commentary, we examine Schaefer’s proposal to apply a hierarchical predictive processing (HPP) framework to research on music perception and music performance. As we shall see, this proposal raises the possibility of enriching this research area with new theoretical and empirical resources from further afield. In order to tap the potential of such a project, it will be important to work towards the formulation of hypotheses that are uniquely generated by the HPP framework. We attempt to contribute to this project by specifying explanatory resources within the HPP framework that are well-suited to formulating such hypotheses, by articulating several novel questions that are generated by the attempt to apply the HPP framework to musical perception and performance, and by identifying potential challenges for such a project to address. We also provide reasons to expect that the HPP framework may be especially fruitful in the context of joint (musical) action.